Prediction and evaluation of pyrimidinones derivatives: DFT analysis, corrosion inhibition, and bioactivity studies - Ahmed M. Wahba; Kamel Shoueir; Abd El-Aziz S. Fouda (Results in Surfaces and Interfaces)
Analyzing binary heterocyclic pyrimidinones using density functional theory (DFT) calculations and Monte Carlo (MC) simulations, as well as assessing their ADME (Absorption, Distribution, Metabolism, and Excretion) and toxicological properties is the objective of this study. A DFT calculation at the B3LYP/6-311G (d,p) level reveals key molecular descriptors, such as energy gap, electronegativity, and hardness, which show HM-1222 exhibits the highest reactivity, attributed to its favorable electronic properties, including a lower energy gap. Monte Carlo simulations demonstrate the adsorption behavior of these compounds on Cu and Al (111) surfaces, with HM-1221 and HM-1223 exhibiting strong interactions, suggesting effective corrosion inhibition. ADME analysis using the Molinspiration toolkit indicates favorable pharmacokinetic profiles for oral administration, while GUSAR software predicts low environmental toxicity levels. These findings underscore the potential of binary heterocyclic pyrimidinones as effective corrosion inhibitors and their suitability for further development in pharmaceutical applications.